2013
DOI: 10.1016/j.fertnstert.2013.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of an excessive response in in vitro fertilization from patient characteristics and ovarian reserve tests and comparison in subgroups: an individual patient data meta-analysis

Abstract: We demonstrate that AFC and AMH add value to female age in the prediction of excessive response and that, for AFC and FSH, the discriminatory performance is affected by female age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
82
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(97 citation statements)
references
References 64 publications
8
82
1
3
Order By: Relevance
“…Consistent with previous systematic reviews and individual patient data meta-analyses (4,23,24), other predictors of ovarian response to gonadotropin stimulation, such as FSH, were shown to be less predictive than AMH in both trials (18,19) and therefore not considered for this evaluation.…”
supporting
confidence: 73%
“…Consistent with previous systematic reviews and individual patient data meta-analyses (4,23,24), other predictors of ovarian response to gonadotropin stimulation, such as FSH, were shown to be less predictive than AMH in both trials (18,19) and therefore not considered for this evaluation.…”
supporting
confidence: 73%
“…Seifer et al first described AMH concentrations corresponding to a number of oocytes retrieved and mature oocytes in infertile women [59]. It has been shown that AMH is a good predictor of high and low ovarian response during ovarian stimulation [27,60]. New ultrasensitive method of measurement of AMH -picoAMH immunoassay -allows estimation of very low AMH concentrations [57].…”
Section: Amh In Assisted Reproductive Technologymentioning
confidence: 99%
“…Seifer i wsp., jako jedni z pierwszych badaczy, opisali, że AMH koreluje z liczbą uzyskanych oocytów u kobiet z niepłodno-ścią [59]. Dotychczasowe badania określają AMH jako czynnik predykcyjny zarówno zwiększonej, jak i zmniejszonej odpowiedzi jajników na stymulację mnogiego jajeczkowania [27,60]. Nowe technikiultraczułe oznaczenie AMH w surowicy krwi metodą picoAMH -pozwalają na wykrycie bardzo niskich stężeń AMH [57].…”
Section: Amh a Metody Wspomaganego Rozroduunclassified
“…In a single-center study with identical ultrasound machines over the study period and identical personnel undertaking the ultrasound scans, many of these limitations are expected to be minimized. This conformity may explain why AFC has performed so well in single-center and individual-patient data meta-analyses of ovarian response prediction (36,37). Despite this strength we still observe poorer model performance in the model that solely incorporated AFC as compared with AMH.…”
Section: Tablementioning
confidence: 63%